So close, yet so far away? the effects of city size, density, and growth on local civic participation - Tavares, António F. (2013)
Recent studies in the U.S. context have suggested that political participation is a function of the size and concentration of a city’s population. Most of this research focuses on the idea that there is an optimal size and concentration of population that favors active political participation in terms of a higher propensity to vote in local elections, contact local officials, and attend community meetings. The conventional argument suggests a negative relationship between city size and political participation that is mitigated to some extent by the deeper social interactions generated by increased population density. We extend this research by also investigating the influence of population growth on the broader concept of civic participation. Civic participation is a multidimensional concept that requires the use of a broad set of indicators. We expand the number of measures to gauge civic participation at the local level by including data on the formation of volunteer associations, volunteer fire brigades and not-for-profit organizations as well as voter turnout. We test the hypotheses derived from extant research using aggregate data collected from Portuguese cities and discuss the implications of our findings for the literature on local civic participation